Oriental Fruit Fly, Bactrocera dorsalis (Hendel) (Insecta: Diptera: Tephritidae) - Howard V. Weems; John B. Heppner; James L. Nation; Thomas R. Fasulo (EDIS)
The oriental fruit fly is a very destructive pest of fruit in areas where it occurs. It is established in numerous areas in Asia, and is often intercepted in the United States, sometimes establishing infestations that were previously eradicated. This revised 6-page fact sheet was written by H. V. Weems, J. B. Heppner, J. L. Nation, and T. R. Fasulo, and published by the UF Department of Entomology and Nematology, March 2012.